Clinical Characteristics of Diabetic Retinopathy Patients in Eye Clinic of Zainoel Abidin General Hospital Banda Aceh, Indonesia - Lia Meuthia Zaini; Sri Marlinda; Annisa Meivira Budiman (Journal of Epidemiology and Public Health, 2020)
Background: Diabetic retinopathy (DR) is one of the most frequent microvascular compli-cations of diabetes mellitus (DM). The increasing number of diabetic retinopathy cases, amajor cause of blindness worldwide, is resulted from the increasing prevalence and life span of diabetes mellitus patients. In 2010, the number of diabetic retinopathy cases was 126.6 million and is predicted to increase to 191.0 million by 2030. The number of patients with visionthreatening diabeticretinopathy is also predicted to increase from 37.3 million to 56.3 million.Subjects and Method: This study was a descriptive study conducted from January to February 2020.A sample of 98 patients was taken through fixed disease sampling. Research data was collected from electonic medical record of patients visiting Eye Clinic of Zainoel Abidin General Hospital Banda Aceh using total sampling method. The researchers used the triangulation method to complete some missing demographic data in the medical records, such as occupation, education, and monthly salary. Interviews were conducted directly with patients after they underwent an examination, and the results were included in the research form. Results: 35 patients (35.7%) were aged 56-65 years and 26 patients (26.5%) worked as house-wives. The most common systemic complications were heart disorder found in 17 patients (17.3%). Proliferative diabetic retinopathy (PDR) was identified in 49 patients (50.0%), whereas 51 patients (52.0%) presented with diabetic macular edema (DME). 44 patients (44.9%) came with less than 6/60 visual acuity on the left eye.Conclusion: Most patients presenting in Eye Clinic of Zainoel Abidin Hospital Banda Aceh were in worse condition (PDR) with visual acuity of less than 6/60. Therefore, educating and counseling diabetic patients to undergo routine screening by ophthalmologists are important in order to prevent loss of vision caused by diabetic retinopathy.Keywords: clinical characteristic, diabetic retinopathyCorrespondence: Lia Meuthia Zaini. Department of Ophthalmology, Faculty of Medicine, Universitas Syiah Kuala/ Dr. Zainoel Abidin hospital. Jl. Tgk. Daud Deureueh 108, Banda Aceh, Indonesia. Email: liamzaini@unsyiah.ac.id. Mobile: +6282266891502.Journal of Epidemiology and Public Health (2020), 05(04)https://doi.org/10.26911/jepublichealth.2020.05.04.12